On the mean-meridional circulation during the summer and winter monsoon seasons - RAO , M. SANKAR; KUSUMA, M. R. (MAUSAM, 1978)
Computation of the mean-meridional circulation within the framework of Kuo's model is carried out for the northern hemisphere and for the globe, for winter and summer seasons. It is inferred that the forcing due to beating plays a dominant role as far as the Hadley cell is concerned. From the computation of global mean-meridional circulation it is concluded that the direct effect of southern hemispheric mechanical forcing on the northern hemispheric circulation is not significant. But the thermodynamical forcing has a great influence on the northern hemisphere circulation.